Comparative Analysis of Clean and Foul Bills of Lading Based on Laboratory Verification of Documents at the Port of Belawan - Ridho, Syarifur; Manullang, Irfan Toro; Maulana, Rio; Chandra H., Michael Ruli (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2025)
This study aims to compare clean and foul Bills of Lading (B/L) using a systematic document analysis approach in a document verification laboratory. A B/L is a key document in cargo transportation that reflects the condition of goods when received by the carrier. A clean B/L indicates that the goods were accepted without any remarks of damage or discrepancy, while a foul B/L includes notes indicating defects or inconsistencies. The research applies a descriptive-comparative method using authentic B/L documents from actual shipping practices. Each document was analyzed in detail to identify structural differences and assess content accuracy. The results show clear distinctions between clean and foul B/Ls, particularly in terms of annotations, layout, and verification process duration. The findings confirm the important role of document laboratories in ensuring the validity and classification of B/Ls. This study contributes to the improvement of documentation accuracy in cargo handling and supports better administrative decision-making in logistics operations.